2016
DOI: 10.2807/1560-7917.es.2016.21.17.30212
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in ranking communicable disease threats: a literature review, 2015

Abstract: The threat of serious, cross-border communicable disease outbreaks in Europe poses a significant challenge to public health and emergency preparedness because the relative likelihood of these threats and the pathogens involved are constantly shifting in response to a range of changing disease drivers. To inform strategic planning by enabling effective resource allocation to manage the consequences of communicable disease outbreaks, it is useful to be able to rank and prioritise pathogens. This paper reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…An elicitation of scientific and technical judgments from experts for infectious disease prioritization has been pursued via numerous methods, including Delphi process and MCDA, in countries such as the United Kingdom, Germany, the Netherlands, and Sweden . A systematic analysis of best practices in prioritizing infectious disease risks identified MCDA as offering a particularly robust methodologic approach, and this method enabled the prioritization presented here. Sourcing expert opinion does have analytical limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An elicitation of scientific and technical judgments from experts for infectious disease prioritization has been pursued via numerous methods, including Delphi process and MCDA, in countries such as the United Kingdom, Germany, the Netherlands, and Sweden . A systematic analysis of best practices in prioritizing infectious disease risks identified MCDA as offering a particularly robust methodologic approach, and this method enabled the prioritization presented here. Sourcing expert opinion does have analytical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the expert group offers a potential source of bias. Ensuring broad geographical representation and multidisciplinary membership of expert panels are among the recommendations in the ECDC best practices framework . Although the group that participated in this workshop was relatively small, bias was mitigated by including participants from multiple European countries and representing expertise in blood transfusion, cells and tissues, organ transplantation, and bacteriology.…”
Section: Discussionmentioning
confidence: 99%
“…104 A review by O'Brien and co-authors examined five prioritization methodologies (Delphi, bibliometrics, qualitative algorithm, multi-criteria decision analysis, and questionnaire studies) described in 17 published studies for ranking communicable disease threats. 105 The authors concluded that no method is superior, but observed that common practices in all methods could be employed in a superior manner.…”
Section: Microbial Risk Modelsmentioning
confidence: 99%
“…However, in low-resource settings, capacity-building efforts should be initially focused on a few key diseases (22). Disease prioritization enables effective capacity building and resource allocation to increase surveillance, guide research, and improve preparedness and response protocols, further advancing global health security and the international health regulations (23)(24)(25).…”
mentioning
confidence: 99%